Research on evaluation of expressway system operation and maintenance resilience based on DBO-ELM model - Zhao, Sanglin; Ye, Jin; Deng, Hao; Huang, Xinyi; Xie, Rong; Long, Xinyi; Gustaf, Måns (Frontiers in Physics, 2025)
As the basic and important service facilities of the national economy, the smooth and safe operation of expressways is of considerable practical significance to promote the stable development of the transportation industry and support the implementation of national strategies. Therefore, in order to improve the ability of expressways to deal with sudden traffic accidents and its operation and maintenance resilience, this study introduces the theory of safety resilience into the safety management of expressway sections, uses word frequency analysis to identify the main factors of high-speed operation and maintenance safety resilience, and constructs an evaluation system of operation and maintenance resilience. An expressway operation and maintenance resilience evaluation model based on improved dung beetle algorithm optimization (WFA-Critical-IAHP-DBO-ELM) was established and applied to a section of the Chang–Zhang Expressway. Compared with the random forest model and XGBoost model, it is proven that the DBO-ELM model has strong generalization ability and evaluation accuracy. This paper proposes a scientific evaluation solution for improving the resilience of expressways and provides a reference for engineering practice.